2009
DOI: 10.1007/s12328-009-0079-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic tumor causing ileoileal intussusception: an unusual cause of an unusual neoplasm in an adult, with a clinicopathological review of the literature

Abstract: An inflammatory myofibroblastic tumor (IMT) of the ileum is a very rare lesion of the gastrointestinal tract. A 36-year-old female presented with abdominal fullness and colicky pain of 5 days' duration. Plain abdominal radiography showed an intestinal obstruction with dilated jejunal loops. Abdominal computed tomography and ultrasonography demonstrated a well-defined intraluminal solid mass surrounded by the typical mural layers of an invaginated ileum. The patient then underwent an exploratory laparotomy unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…A previous study has reported that only 1.2% of IMTs arise from the small intestine 3 . It has been described that IMTs in the small bowel can cause intestinal obstruction due to intussusception 1 . However, in our case a conglomerate of small bowel was the cause of ileus, which to our knowledge has not been presented previously in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study has reported that only 1.2% of IMTs arise from the small intestine 3 . It has been described that IMTs in the small bowel can cause intestinal obstruction due to intussusception 1 . However, in our case a conglomerate of small bowel was the cause of ileus, which to our knowledge has not been presented previously in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The tumors are widely acknowledged as benign but with a potential to recur at the primary site. Approximately 8-25% recurs locally 1,4 . Rare examples and/or with metastasis 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammatory myofibroblastic tumors (IMTs) are rare mesenchymal neoplasms composed of proliferating myofibroblastic spindle cells, and an accompanying inflammatory -usually chronicinfiltrate 1 . The etiology of IMTs is unknown, but an association with Wilms' tumor, the most common primary renal malignancy in children, has been suggested 2,3 .…”
Section: Introductionmentioning
confidence: 99%